MODEL MULTIVARIATE FAKTOR PENENTU KEPERCAYAAN DIRI PEDAGANG KECIL DI BANYUMAS - Herman Sinaulan (Performance: Jurnal Personalia, Financial, Operasional, Marketing dan Sistem Informasi, 2015)
Small Businesses are growing in importance. Hundreds of small businesses openevery month. Small business as one that is independently owned and operated are 402units in Banyumas Regency. Some factors have influenced the small businesses growth.The purpose of this research is to analyze the influence of motivation and internal locusof control with moderation of commitment toward the self-efficacy of the smallbusinessmen in Banyumas Regency.The result of this research shows that self-efficacy of the small businessmen aredirectly influenced by motivation and internal locus of control. Relationships betweenmotivation and self-efficacy are moderated by the commitment, but the relationshipsbetween internal locus of control and self-efficacy aren’t moderated by the commitmentof the owners.